Straw Hocol Tech / Muhammad Adli Budin - Budin, Muhammad Adli (2020)
Nowadays people are concerning about our nature. Our Straw Hocol Tech will provide clean water without using electricity. We can save a lot of electricity Eco-friendly to the public community especially for hikers, and backpackers. The simple design and small in size of Straw Hocol Tech make it very suitable and easier to bring anywhere. This lamp convert the light energy from the sunlight and convert it to energy. The main reason that makes it original is that the ability to filter out waterborne viruses, as this is very crucial for in developing country or rural areas. Viruses are classified as pathogenic microorganisms, small creatures that can cause disease when consumed and can be spread between humans and animals by means of body fluids and waste that make it into the water supply. As the sizes of viruses can be as small as 0.01 microns, as our product can filter out small particles up to 0,05 microns, so it is suitable to removed it completely. Our product is designed for use in the rural areas In other areas where sanitation and sewage systems may be more developed but not actively maintained, it is common for underground pipes to leak resulting in cross contamination between the clean water and wastewater pipes. These wastewater pipes often carry viruses from human waste that contaminate the tap supply. Our product is essential for hikers and backpackers as there are limited source of clean water in the forest or jungle, eventhough that the water may semm clear and safe to drink, as study shows that, in the river, there a lor of microorganms can be found in the water. The clearer state of water doesn’t mean it is a safe to be drink directly. So our product will help to filter out all the microorganisms as this is also make it easier for them, because they did not need to bring along water bottle with them. This product has function and advantages that are not found in today’s technology.